One-pot Synthesis and Photoswitching Properties of Bis-triazole-linked Macrocyclic Glycoazobenzene - Ludwig, Corentin; Li, Gaoyu; Retailleau, Pascal; Maisonneuve, Stéphane; Xie, Juan (Synthesis, 2025)
Photoswitchable glycomacrocycles are of great interest because of their intrinsic chirality, their variable ring sizes, molecular shapes, and their potential applications in chemistry, materials science, biology, and drug discovery. Through a one-pot double click reaction, we have successfully synthesized a new 20-membered azobenzene-based glycomacrocycle bearing two triazole rings. The macrocyclization conditions have been optimized to achieve a yield of up to 55% for the synthesis of hundreds of milligrams of the compound E-1. The macrocyclic glycoazobenzene E-1 can be reversibly photoisomerized between E and Z isomers, with good photoconversion yields, high fatigue resistance, and bistability of both E and Z isomers. The X-ray structures have been obtained for both E- and Z-isomers of 1. The chiroptical activity has also been observed with the E-1.
Keywords: Azobenzene (AB), Chiroptical property; Click reaction; Glycomacrocycle; Photoswitching